2021
DOI: 10.1007/s40843-020-1623-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inheritance from methylene blue to carbon dots against reduction, aggregation, and DNA interference

Abstract: Photodynamic therapy (PDT) is a treatment that uses light-sensitive drugs and a light source to destroy cancer cells. Methylene blue (MB) is an efficient photosensitizing agent that has been widely used in PDT. However, MB suffers from the hypochromic effect that is caused by self-aggregation and DNA binding in vivo. It is also easily reduced to ineffective leucomethylene blue in the hypoxic environments surrounding solid tumors. In this work, we prepared MB carbon dots (MB-CDs) using MB as the carbon source. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The concentration of Mn/HA-CDs increases the rate of apoptosis. Moreover, preliminary tests on the ability to detect apoptosis by co-incubating HepG2 cells with Mn/HA-CDs and HA-CDs, the calcein-AM/PI assay were conducted (Figure e). , Incubation of living cells with Mn/HA-CDs and HA-CDs without irradiation results in intense green fluorescence, which is typical of calcein-AM-stained cells under dark conditions, which indicates very little cytotoxicity. However, the red fluorescence signal observed for PI, dead cells in the Mn/HA-CD group is higher than that for the HA-CD group upon exposure to visible light for 12 min, clearly indicating that Mn/HA-CDs have a higher ability of phototoxicity to cause cell apoptosis …”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Mn/HA-CDs increases the rate of apoptosis. Moreover, preliminary tests on the ability to detect apoptosis by co-incubating HepG2 cells with Mn/HA-CDs and HA-CDs, the calcein-AM/PI assay were conducted (Figure e). , Incubation of living cells with Mn/HA-CDs and HA-CDs without irradiation results in intense green fluorescence, which is typical of calcein-AM-stained cells under dark conditions, which indicates very little cytotoxicity. However, the red fluorescence signal observed for PI, dead cells in the Mn/HA-CD group is higher than that for the HA-CD group upon exposure to visible light for 12 min, clearly indicating that Mn/HA-CDs have a higher ability of phototoxicity to cause cell apoptosis …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was reported that they exhibit significant resistance to intervention from DNA interaction, agglomeration, and reduction. In a study by Xu et al, the MB-CDs demonstrated convincing ability for the photodynamic therapy, both in vivo as well as in vitro [323].…”
Section: Role Of Cds In Photodynamic Therapymentioning
confidence: 96%
“…Photosensitizers like methylene blue (MB) has been broadly exploited to develop effective photodynamic therapy, although the limitation of using MB individually resides in its hypochromic effect produced due to its binding with DNA in vivo, and selfagglomeration [323]. Therefore, such photosensitizers, when combined with carbon-based nanomaterials like CDs, could display low cytotoxicity, as well as excellent biocompatibility to introduce novel photodynamic therapy.…”
Section: Role Of Cds In Photodynamic Therapymentioning
confidence: 99%
“…Thus, combining CDs with traditional photosensitizers is an effective strategy to improve PDT efficiency. [250][251][252] In addition, the water solubility provided by CDs allows CDs@PS to be used in biological applications where the PS alone cannot due to its low solubility. Many attempts have been made to functionalize CDs with molecular dyes (chlorin, porphyrin, and BODIPY derivatives).…”
Section: Anticancermentioning
confidence: 99%